La production animale au Mali central: Enquete preliminaire sur la production avicole villageoise dans la region de Niono - Kuit, H.G.; Traoré, A.; Wilson, R.T. (CIPEA, 1985)
Reports results of a study carried out in Niono, Mali to collect data on ownership patterns, management strategies and objectives of poultry kept under social and environmental conditions typical of much of Africa.